Experimental and numerical assessment of flange plate reinforcements on square hollow section T joints. (October 2018) - de Lima, L.R.O.; Guerrieiro, L.C.B.; da S. Vellasco, P.C.G.; Costa-Neves, L.F.; da Silva, A.T.; Rodrigues, M.C.
Abstract: Safety and economy are vital issues that any method should account for in the structural design of tubular elements. In some cases, the use of flange plates as reinforcement improves the tubular joint resistance and is an economical alternative to changing the section of chords or braces. This paper presents an experimental and numerical investigation aiming at evaluating possible benefits of this plate reinforcement on the joint's ultimate capacity and overall structural response. The research focused on the static behaviour of axially compressed T joints with a flange plate reinforcement, and the variables were the reinforcement plate length and boundary conditions. The structural response of the studied reinforced joints was compared to their unreinforced counterparts to evaluate the magnitude of the enhancement in the joint performance. The experimental results were compared to the Eurocode 3, ABNT NBR 16239 and ISO 14346 design recommendations, as well as alternative design formulae found in the literature. These comparisons indicated that the strength predictions provided by analytical models available for these joints might substantially underestimate the experimental findings. Finally, an alternative formulation is proposed based on Eurocode 3 and ABNT 16239 design recommendations to estimate the resistance of T joints reinforced with flange plates. Highlights: Experimental tests to investigate T joints reinforced by a flange plate. A finite element model was validated against experimental results. A parametric analysis enables the increasing of the results. An equation was developed to assess the resistance of reinforced SHS T joints.